Effectiveness and utility of percolation tanks of percolation tanks in Malwa and Nimar region - Ranade, D H; Jadav, M L; Swarup, Indu; Bhagat, D V; Girothia, O P (Indian Farming, 2019)
The team of All India Coordinated Research Project for Dryland Agriculture, College of Agriculture, Indore, have been regularly visiting different villages of various districts of Malwa and Nimar region to assess farmers’ priorities and problems related to agriculture. Initially during 1990, it was desired by the farmers that project should attempt to enhance the irrigation water availability and should provide improved varieties of different crops for increasing agricultural production and income. Thus, through ICAR supported and State financed watershed programmes, number of water-harvesting tanks were constructed mostly on government land for providing irrigation water to farmers. The improved varieties of different crops like soybean, chickpea, maize, etc. enhanced the farm productivity and income with the help of supplemental water through water-harvesting tanks.